Structural performance of buried prestressed concrete cylinder pipes with harnessed joints interaction using numerical modeling. (January 2016) - Hajali, Masood; Alavinasab, Ali; Abi Shdid, Caesar
Graphical abstract: Highlights: Advanced modeling of buried prestressed concrete cylinder pipes (PCCP) using FEM. Modeling interaction between pipes at harnessed joints. Modeling pipe soil interaction along with internal and external loads. Evaluating how the extent and location of PCCP damage affect failure pressure. Abstract: Broken prestressing wire wraps are the main cause of failure in buried prestressed concrete cylinder pipes (PCCP), which form the backbone of water and wastewater infrastructure networks in North America. Advanced numerical modeling using non-linear finite elements is used to model the effect of the number and location of broken wire wraps on the structural performance of Class 125-14, 96-in. PCCP. The modeling technique used is unique in that it considers full interaction between adjacent pipes with harnessed joints, as well as combined internal and external loading with full soil–pipe interaction. Performance indicators in the various components of PCCP are monitored as internal pressure is increased. A sensitivity analysis is presented for how manipulating the severity of the damage affects the failure pressure of the pipe. The results show that the internal fluid pressure required to cause failure can be as much as 34% lower when the damage is at the barrel of the pipe, and that the internal pressure that causes yielding of the wire wraps decreases by 66% as the damage worsens from 5 to 100 wire breaks.